STRATEGY FOR INCREASING INTEREST IN READING THE YELLOW BOOK OF STUDENTS AT THE AL-FATTAH 3 SIMAN LAMONGAN ISLAMIC BOARDING SCHOOL - Surya Hidayati; Muhammad Subhan; Sutarno Sutarno; Sariman Sariman (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
This article aims to describe the planning and implementation of learning activities in improving the reading quality of the yellow book at the Al-Fattah 3 Siman Sekaran Lamongan Islamic boarding school and to analyze the pedagogic competence of teachers in the yellow book learning activities at the Al-Fattah 3 Siman Sekaran Lamongan Islamic boarding school. This study uses a descriptive qualitative approach using a type of research, namely a case study. Data collection techniques were carried out using unstructured interviews, participant observation, and documentation. This article produces: (1) planning of learning activities in improving the quality of reading the yellow book at the Al-Fattah 3 Siman Sekaran Lamongan Islamic boarding school is carried out by preparing books according to the specified curriculum and the process of learning activities is guided by the book being taught with the main target being able to memorize and understand the meaning in it so that they are able to practice it in their lives. (2) Teacher pedagogic competence in learning the yellow book at Pondok Pesantren Al-Fattah 3 Siman Sekaran Lamongan is included in the good category because almost all of it is implemented.